The Importance of Monitoring Blood Glucose Test in Patients Post-operative Coronary Artery Bypass Graft Surgery - Dayoko, Abit Mawan; Gunarti, Tri; Putri, Fitria Habibah Nita Yuliana Eka (Care : Jurnal Ilmiah Ilmu Kesehatan, 2024)
Hyperglycemia is a risk factor for cardiac surgery-associated acute kidney injury in post-operative coronary artery bypass graft surgery patients. Glycemic control is important to prevent cardiac surgery-associated acute kidney injury. Postoperative glycemic control suggested 110-150 mg/dL. The aims of this study were to lower blood glucose levels and reduce the risk of occurrence or severity of cardiac surgery-associated acute kidney injury in post coronary artery bypass graft surgery patients. This study was conducted with a case study design involving 2 post operative coronary artery bypass graft patients who experienced hyperglycemia on the 1st to the 3rd day of treatment. Data collection was carried out from May 22 to May 23, 2023. The results of the case study showed that monitoring blood glucose in post-cardiac surgery patients is very important. Both patients experienced hyperglycemia in the early postoperative phase. With close monitoring and administration of insulin therapy according to the doctor's advice, the blood sugar levels of both patients were controlled. Monitoring urine output and evaluating serum creatinine levels showed that the first patient had cardiac surgery-associated acute kidney injury stage 1 on day 2 and showed improvement on day 3. The second patient did not develop cardiac surgery-associated acute kidney injury. The role of critical nurses in monitoring blood glucose levels and administering insulin doses is supported by related research. Strict monitoring and target ranges of blood glucose levels, in collaboration with the medical team are necessary to reduce the risk of cardiac surgery-associated acute kidney injury events.